Assessment and optimization of a novel waste heat stepped utilization system integrating partial heating sCO2 cycle and ejector refrigeration cycle using zeotropic mixtures for gas turbine. (15th February 2023) - Jiang, Yuemao; Ma, Yue; Han, Fenghui; Ji, Yulong; Cai, Wenjian; Wang, Zhe
Abstract: A waste heat stepped utilization system integrating a partial heating sCO2 power cycle and a thermally-driven ejector refrigeration cycle is proposed for gas turbine performance enhancement. The gas turbine exhaust heat is stepped utilized by two gas heaters in the sCO2 power cycle and a waste heater. Then, the exhaust CO2 heat is cascade utilized by the ejector refrigeration cycle using zeotropic mixtures (R245fa/R1234ze) as its working fluid. Detailed energy, exergy, and economic models are built to conduct the system performance investigation. The results show that the proposed system can improve the thermal and exergy efficiency by 28.23% and 2.65% compared with the single sCO2 cycle. The parametric study discloses that there are optimal turbine inlet temperature and compressor inlet pressure for power output and optimal refrigerant mixture ratio, around 0.30, for cooling capacity. Further, multi-objective optimization is implemented, and the overall system efficiency, bottoming system exergy efficiency, and levelized cost of exergy can reach 62.15%, 45.22%, and 0.076 $/kWh, respectively. Finally, to prove the superiority of the integrated system for different application scenarios, the system performance is optimized in the gas turbine part-load. The results reveal that the proposed system can effectively improve the gas turbine performance, especially in the part-load. Under all the gas turbine loads, the proposed system's levelized cost of exergy is no more than 0.076 $/kWh, which provides theoretical references for the development of the gas turbine combined system in practical engineering. Graphical abstract: Image 1 Highlights: An exhaust gas waste heat stepped utilization system is proposed for gas turbines. ERC with innovative environmental-friendly zeotropic mixtures was explored in depth. System superiority is proved by comparative thermoeconomic analysis and comparison. Three-objective optimization is performed under the gas turbine full and part load.